CREATING URBAN GROWTH SIMULATION MODELS DRIVEN BY THE BOSPHORUS BRIDGES - Ayazli, Ismail Ercument; Kilic, Fatmagul; Lauf, Steffen; Kleinschmit, Birgit; Demir, Hulya (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
In the past and today, Istanbul has always been one of the most important cities in the world because of its historical, cultural and natural features. This fact has caused increase in population and great transportation problem since 1950s. To surmount the transportation problem, two bridges were built and a third one is being constructed on the Bosphorus. Although zone plans, which made in the 1960s, suggested the urban growth to east-west direction, each bridge created its own traffic and triggered urbanization to northward. Main objectives of this paper are to determine the land use changes driven by Bosphorus bridges, predict potential impacts of the 3rd bridge and compare the effects of different routes on urbanization in Istanbul. Two motorways were selected among for alternative routes preparing for 3rd bridge. To find out the impacts of Bosphorus bridges on the urbanization, cellular automata (CA) based urban growth simulation models were created for the year 2030 and change detection analysis were implemented between 2009 and 2030. According to the results, Istanbul will continue grow northward and almost the half of forest area will be damaged and transformed to urban area in 2030.
Keywords: Simulation; Urban Growth Model; Cellular Automata; LULC Change; URBANIZATION; Environmental Sciences & Ecology